Distribution of forest litter and live ground cover biomass in northern taiga of the Central Evenkia depending on relief - O. V. Sergeeva; L. V. Mukhortova; L. V. Krivobokov (Сибирский лесной журнал, 2020)
Live ground cover and litter play an important role in forest ecosystems, especially in northern boreal subzone where phytomass of understory vegetation and its annual turnover are comparable with those of tree stands. However, there are practically no quantitative estimates of live ground cover biomass and forest litter stock for different types of forest ecosystems in the Central Siberia permafrost zone. The study was conducted in the Central Evenkia which territory has well developed low-mountain relief. The last one contributes to microclimatic diversity and thus differences in dynamics of phytomass accumulation and plant residues’ decomposition between landforms. The litter stocks and live ground cover biomass were assessed for forest stands growing in the lowlands, on the slopes of northern and southern exposition and on the uplands. The studied ecosystems have been unaffected by forest fire for more than 50 years now. The main forest-forming species of all forest phytocenoses except for upland is Gmelin’s larch Larix gmelinii (Rupr.) Rupr. It was found that among the studied ecosystems the highest values of live ground cover biomass and forest litter stock occur in the lowlands and on the northern slopes. Such distribution is the consequence of these landforms’ hydrothermal conditions: permafrost here lies closer to the surface and soils are permanently wet. These factors create favorable conditions for moss-lichen cover growth but retard decomposition of plant residues leading to forest litter accumulation. It is noted that mosses and subshrubs make the major contribution to the live ground cover biomass in the studied ecosystems. The main components of litter in forest phytocenoses of the Central Evenkia are fermented plant residues.